Mast Cell Subsets and Their Functional Modulation by the Acanthocheilonema viteae Product ES-62 - Dimity H. Ball; Hwee Kee Tay; Kara S. Bell; Michelle L. Coates; Lamyaa Al-Riyami; Justyna Rzepecka; William Harnett; Margaret M. Harnett (Journal of Parasitology Research)
ES-62, an immunomodulator secreted by filarial nematodes, exhibits therapeutic potential in mouse models of allergic inflammation, at least in part by inducing the desensitisation of FcεRI-mediated mast cell responses. However, in addition to their pathogenic roles in allergic and autoimmune diseases, mast cells are important in fighting infection, wound healing, and resolving inflammation, reflecting that mast cells exhibit a phenotypic and functional plasticity. We have therefore characterised the differential functional responses to antigen (via FcεRI) and LPS and their modulation by ES-62 of the mature peritoneal-derived mast cells (PDMC; serosal) and those of the connective tissue-like mast cells (CTMC) and the mucosal-like mast cells derived from bone marrow progenitors (BMMC) as a first step to produce disease tissue-targeted therapeutics based on ES-62 action. All three mast cell populations were rendered hyporesponsive by ES-62 and whilst the mechanisms underlying such desensitisation have not been fully delineated, they reflect a downregulation of calcium and PKCα signalling. ES-62 also downregulated MyD88 and PKCδ in mucosal-type BMMC but not PDMC, the additional signals targeted in mucosal-type BMMC likely reflecting that these cells respond to antigen and LPS by degranulation and cytokine secretion whereas PDMC predominantly respond in a degranulation-based manner.